Numerical simulation analysis of the flow field and convective heat transfer in new super open rack vaporizer. (5th August 2016) - Deng, Zhian; Hui, Kai; Zhang, Yan; Cao, Yanqiang
Graphical abstract: Fig. 1 illustrates the geometry of new superORV heat transfer tube. As shown in Fig. 1, the lower half of the heat transfer tube is designed to be a duplex tube configuration differently from the upper section. The lower and upper parts of the heat transfer tube are called "vaporizing section" and "heating section" respectively. The vaporizing section consists of an outer tube with petal-shaped internal fin and similar triangular external fin, and an inner tube with double twisted tape inserts. The heating section is only a circular tube with petal-shaped internal fin and similar triangular external fin, where cross-shaped twisted tape inserts are applied. As shown in Fig. 2, in the present model, a cross-shaped twisted tape insert with a helix angle of 45° was chosen for inner tube, which is used to further improve the heat transfer efficiency of heat transfer tube. Highlights: A new superORV model is proposed. The cross-shaped twisted tape insert. The numerical analysis is applied. A comparative parameter model is developed in this paper. Abstract: With the rapid development of Chinese natural gas industry, vaporizer as the key equipment is used to regasify LNG to meet the requirement of fuel gas in industrial and domestic purposes. In this paper, a new super open rack vaporizer (SuperORV) model is proposed, added a cross-shaped twisted tape insert to the inner tube based on the conventional vaporizer heat transfer tube. Physical and mathematical models are established, the results from the model exhibit a good agreement with experiment data, which implies the calculation model is reliable. Base on this, the heat transfer process of two kinds of superORV heat transfer tube is simulated numerically. The temperature profiles along the heat transfer tube are obtained, the heat transfer performance and the local heat transfer are analyzed, the heat transfer coefficient profiles against temperature and heat transfer tube length are also discussed. The effects of superORV heat transfer tube with LNG pressure and screw pitch are obtained. The results show that the cross-shaped twisted tape insert has a significant effect on enhancing heat transfer performance of new heat transfer tube. The heat transfer performance of new super open rack vaporizer is visible.